Efecto de nemátodos entomopatógenos sobre el gusano cogollero del maíz (Spodoptera frugiperda Smith, 1797) en condiciones in vitro - González Muñoz, Manuel Antonio (2023)
Among the main crops produced in our province of Loja is corn, which is attacked by various pests and diseases; one of the most important pests is the corn earworm, which causes losses of up to 34% in production. For this reason, our study seeks to minimize the damage caused by Spodoptera frugiperda in a biological way without causing impact to the environment,so the objective of this work is to evaluate the mortality of the larvae of the corn earworm Spodoptera frugiperda due to the entomopathogenic nematode's (NEP's) Heterorhabditis bacteriophora under in vitro conditions. For this purpose, the rearing of this insect with a diet based on higuerilla (Ricinus communis) was established, as was the rearing of Galleria mellonella (by means of an artificial diet) for the production of the nematodes. In which it was possible to obtain up to 90 532 NEP´s/larva, the nematodes obtained were used for the biological control of the corn earworm, with a concentration of 0, 400, 800, and 1200 NEP´s per treatment. At 96 hours of evaluation, a mortality of 54. 75, and 84% was obtained for each of the concentrations mentioned above. Where significant differences were observed between the treatments used, the treatment in which 1200 NEP´s were inoculated was the best controller of Spodoptera frugiperda. In the present study, it was possible to know that the biological control is efficient, concluding that NEP´s are a microorganism that controls insect pests. Key words: Wax moth, corn bud, petri dishes, Steinernema, Photorhabdus luminescens.